1999
DOI: 10.1038/sj.jea.7500051
|View full text |Cite
|
Sign up to set email alerts
|

Population-based dietary intakes and tap water concentrations for selected elements in the EPA Region V National Human Exposure Assessment Survey (NHEXAS)

Abstract: A National Human Exposure Assessment Survey ( NHEXAS) field study was performed in U.S. Environmental Protection Agency (EPA) Region V, providing population-based exposure distribution data for selected elements in several personal, environmental, and biological media. Population distributions are reported for the 11 elements that were measured in water and dietary samples. Dietary intakes and home tap water concentrations of lead, arsenic, and cadmium were further examined for intermedia associations, for dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 5 publications
7
26
1
Order By: Relevance
“…Median and mean values for As, Cr, Cu, and Zn concentrations lie within the range of concentrations reported in the literature (O'Rourke et al, 1999;Thomas et al, 1999;Seifert et al, 2000;Divrikli and Elci, 2002;Sofuoglu et al, 2003;Tamasi and Cini, 2004;Gu¨lbahar and Elhatip, 2005;Xu et al, 2006). In the case of Mn, the mean concentration obtained in this study was about seven times smaller than the value reported by Thomas et al (1999).…”
Section: Trace Metal Concentrationssupporting
confidence: 82%
See 3 more Smart Citations
“…Median and mean values for As, Cr, Cu, and Zn concentrations lie within the range of concentrations reported in the literature (O'Rourke et al, 1999;Thomas et al, 1999;Seifert et al, 2000;Divrikli and Elci, 2002;Sofuoglu et al, 2003;Tamasi and Cini, 2004;Gu¨lbahar and Elhatip, 2005;Xu et al, 2006). In the case of Mn, the mean concentration obtained in this study was about seven times smaller than the value reported by Thomas et al (1999).…”
Section: Trace Metal Concentrationssupporting
confidence: 82%
“…In the case of Mn, the mean concentration obtained in this study was about seven times smaller than the value reported by Thomas et al (1999). This number would drop to five if only the mean Mn concentrations of flushed tap water samples were taken into consideration for both studies.…”
Section: Trace Metal Concentrationscontrasting
confidence: 39%
See 2 more Smart Citations
“…Drinking water concentrations are obtained from regulatory monitoring databases (such as SDWIS/FED-USEPA, 2006a) or field study measurements (such as the National Human Exposure Assessment Survey (NHEXAS)- Thomas et al, 1999;Pellizzari and Clayton, 2006). If such data are not available, the drinking water distributions are modeled using the EPANET2 model (Rossman, 2000) with treatment plant data to obtain drinking water concentrations (see e.g., Maslia et al, 2000 for a discussion of application of drinking water distribution modeling to epidemiological studies).…”
mentioning
confidence: 99%